Low Merlin expression and high Survivin labeling index are indicators for poor prognosis in patients with malignant pleural mesothelioma. Issue 8 (25th June 2016) - Meerang, Mayura; Bérard, Karima; Friess, Martina; Bitanihirwe, Byron K.Y.; Soltermann, Alex; Vrugt, Bart; Felley-Bosco, Emanuela; Bueno, Raphael; Richards, William G.; Seifert, Burkhardt; Stahel, Rolf; Weder, Walter; et al.
Abstract : Introduction: Alterations of the tumor suppressor Neurofibromatosis type II (NF2) have been reported in about 40% of Malignant pleural mesothelioma (MPM) patients. NF2 (Merlin) deficiency leads to alterations of the Hippo pathway; resulting in activation of the oncogenic Yes Associated Protein‐1 (YAP1). Our aim was to investigate the association between these alterations and clinical outcomes. Material and methods: Tissue microarrays composed of MPM tumors derived from 2 independent MPM cohorts were employed for this study. Immunohistochemical expression of Merlin, YAP1 and its target genes, Survivin and connective tissue growth factor (CTGF) were assessed in nuclear and cytoplasmic fractions. Cohort 1 was comprised of 145 patients intended to be treated with chemotherapy (CTX) followed by extrapleural pneumonectomy (EPP), thus both pre‐ and post‐CTX tissues were available. Cohort 2 was comprised of 59 patients treated with EPP followed by intraoperative hyperthermic cisplatin and/or adjuvant CTX and/or radiotherapy. Marker expression was quantified by means of labeling index (%) for nuclear Survivin and by H‐score for the other markers. The dichotomized marker expression was tested for the association with overall survival (OS) and freedom from recurrence (FFR). Results: Kaplan–Meier survival curves revealed a significant association between low cytoplasmic Merlin expression in pre‐induction CTX tissues of cohort 1 with shorter FFR (p = 0.02) and OS (p = 0.03). The same tendency was observed in the chemotherapy naïve tissues obtained during EPP of cohort 2. Low nuclear Merlin expression in post‐CTX tissues (available from cohort 1 only) was associated with shorter FFR (p = 0.04) and OS (p = 0.05). High nuclear Survivin labeling indices in both pre‐ and post‐CTX tissues of cohort 1 was associated with shorter FFR (p = 0.02). In cohort 2, this was associated with both FFR and OS (p = 0.046 and p = 0.002, respectively). In multivariate analysis, low expression of cytoplasmic Merlin remained an independent prognosticator for shorter FFR of cohort 1 [hazard ratio (HR) = 0.5, 95% confidence interval (CI) = 0.3–0.9, p = 0.001] and OS [HR = 0.5, 95% CI = 0.3–1, p = 0.04]. High Survivin labeling index was an independent prognostic factor for shorter FFR in patients from cohort 1 [HR = 3.4, 95% CI = 1.7–6.8, p = 0.006] and shorter OS in patients from cohort 2 [HR = 2.35, 95% CI = 1.27–4.33, p = 0.006]. Conclusions: Our findings uncover the significance of Merlin protein expression and Survivin labeling index as prognosticators for poor clinical outcome in two independent MPM cohorts. If confirmed, these markers may be used to identify subgroups of patients benefitting from additional treatment. Highlights: Merlin and the Hippo pathway are prognostic factors for Malignant Pleural Mesothelioma. Low cytoplasmic Merlin expression at diagnosis is associated with shorter survival. A high nuclear Survivin labeling index is associated with shorter survival. The data was confirmed in 2 patient cohorts undergoing different treatment regimens.